Disentangling Environmental Drivers of Phytoplankton Biomass off Western Iberia - Ferreira, A.; Garrido-Amador, P.; Brito, Ana C. (Frontiers in Marine Science, 2019)
Phytoplankton are the main primary producers in marine ecosystems, supporting important food webs. They are recognized as important indicators of environmental changes in oceans and coastal waters. Ocean colour remote sensing has been extensively used to study phytoplankton throughout the world, yet there is still much to understand in terms of what influences phytoplankton variability at regional scales. The main aim of this study was to investigate the drivers of phytoplankton variability in the Western Iberian Coast (WIC), for the period 1998-2016. Satellite chlorophyll a (CHL) data was acquired from the Copernicus Marine Environment Monitoring Service (CMEMS). A positive annual trend of CHL was observed at the northern coastal WIC, near Galicia, and a negative trend was observed in southern areas, near the Gulf of Cádiz. An empirical Orthogonal Function (EOF) analysis was implemented to identify regions with similar patterns of CHL variability. Six regions were obtained. A set of climate indices, satellite and model variables were then used as environmental predictors in Generalized Additive Models (GAMs) that explained between 18.0 to 49.3% of the total variance of CHL anomalies calculated from a detrended and deseasoned dataset. In the northern oceanic region positive anomalies were linked to high North Atlantic Oscillation (NAO) values and negative anomalies to high mixed layer depths. In the southern oceanic region, positive CHL anomalies were found to be associated with high concentrations of nitrogen, that may indicate nitrogen limitation. Phytoplankton in coastal areas were found to respond to basin-wide (e.g. Atlantic Multidecadal Oscillation-AMO) and coastal processes (e.g. upwelling and continental runoff), yielding positive anomalies with low salinity values. In very small coastal areas near major rivers, such as Douro and Guadalquivir, the positive response of phytoplankton to increased nitrogen concentrations and decreased salinity was evident. Considering the changes in climate expected for this region, related to the decrease in precipitation and increase in summer temperatures, as well as some apparent weakening of upwelling, possible significant impacts on the phytoplankton community can be anticipated. These results are therefore also relevant for environmental management, especially in the context of the European Marine Strategy Framework Directive (MSFD).